The effect of performance indicators on the time the first goal is scored in football matches. (1st April 2016) - Pratas, José Maria; Volossovitch, Anna; Carita, Ana Isabel
Abstract : Scoring the first goal in football could be crucial for winning a match. The aim of this study was to identify the performance indicators that influence the time the first goal is scored in high-level football matches. A total of 240 matches of the Portuguese Premier League played in 2009/10 season were analysed. The difference between the total number of goals scored and conceded during the competition up until the match considered, total ball possession time, shots on goal, set plays, disciplinary sanctions and substitutions were selected as predictor variables for the time the first goal is scored and loaded on a Cox regression model with time-dependent covariates. A greater goal difference (p < 0.05) and a larger number of shots on goal (p < 0.01) had a positive significant influence on the time the first goal was scored in the match by home teams; at the same time disciplinary sanctions (p < 0.01) and substitutions (p < 0.01) had a negative significant effect on the time of the first goal.